2014
DOI: 10.4168/aair.2014.6.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Exhaled Nitric Oxide and Impulse Oscillometry in Children With Allergic Rhinitis

Abstract: PurposeAirway inflammation, bronchial hyper-responsiveness (BHR), and bronchodilator response (BDR) are representative characteristics of asthma. Because allergic rhinitis (AR) is a risk factor for asthma development, we evaluated these 3 characteristics in AR using measurement of fractional exhaled nitric oxide (FeNO), a methacholine challenge test (MCT), and impulse oscillometry (IOS).MethodsThis study included 112 children with asthma (asthma group), 196 children with AR (AR group), and 32 control subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
1
15
0
6
Order By: Relevance
“…A specific IgE was measured for 6 common allergens in Korea: Dermatophagoides pteronyssinus , Dermatophagoides farina , egg whites, cow milk, German cockroach, and Alternaria alternata . [16] This study was approved by the Institutional Review Board of Severance Hospital (protocol no. 4-2004-0036).…”
Section: Methodsmentioning
confidence: 99%
“…A specific IgE was measured for 6 common allergens in Korea: Dermatophagoides pteronyssinus , Dermatophagoides farina , egg whites, cow milk, German cockroach, and Alternaria alternata . [16] This study was approved by the Institutional Review Board of Severance Hospital (protocol no. 4-2004-0036).…”
Section: Methodsmentioning
confidence: 99%
“…Although the literature on FeNO measurement in children with AR is less extensive, FeNO is increased in children with AR. 57,58 A considerable body of evidence suggests that rhinitis and asthma represent the manifestations of one airway disease of common pathogenic pathway with a wide spectrum of severity. 59 Increased FeNO in patients with AR probably reflects the extension of inflammation throughout the airways, a feature in the well-known concept of the 'united airway. '…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…Increased FeNO was observed in AR with and without BHR . Children with AR and BHR had slightly higher FeNO values than patients without BHR.…”
Section: Lower Airway Inflammatory Involvement In Rhinitismentioning
confidence: 79%
“…Kim et al . observed that the bronchodilator response in reactance at 5 Hz (Δ ×5) and the reactance area (Δ AX) increased more in the asthma and AR groups than in the controls.…”
Section: Subclinical Impairment Of Lung Functionmentioning
confidence: 99%